Design and Development of a IoT-Based Moisture Detection Device for Corn Seeds - Guguh Makbul Rahmadani Fitra; Sunardi Sunardi (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
Lately the planting of corn has increased and increased in several areas. The increasing popularity of corn is due to its high economic value. Corn that has been harvested cannot be sold immediately because it must meet certain moisture content requirements. Farmers must know the maximum value of the moisture content in the corn kernels resulting from the harvest to meet one of the standards set by the industry. The water content contained in corn kernels can have a big influence on determining its quality or selling value. This study aims to design and implement a device for detecting the moisture content of corn kernels as a tool to help farmers produce dry and good quality corn kernels. This research uses an Internet of Things (IoT) based method by sending the corn moisture content and ambient air temperature values to a mobile phone via the Blynk application. The components used are the NodeMCU ESP2866 microcontroller, YL-69 sensor, DHT-22 sensor, 16x2 I2C LCD, and battery. The results of this study have been able to make a water content detector tool on corn kernels based on IoT that can work well. From several tests carried out at night and in the morning, a low error rate of 2.3% was found on the DHT-22 sensor, while on the YL-69 sensor the tests were carried out on three types of corn samples, namely dry, medium, and dry corn kernels. and wet obtained a low error rate of 3.1%.